Structural investigation of sparfloxacin drug using mass spec-trometry and MNDO semi-empirical molecular orbital calcu-lations - Sarhan Mahmoud Abd El-kareem, Mamoun; ElDesawy, Mohamed; Hawash, Mohamed; Fahmy Ahmed, Magd El dain (International Journal of Advanced Chemistry, 2018)
Sparfloxacin is a broad spectrum antibacterial fluoroquinolone against some microorganisms including gram-positive and gram-negative bacteria and exhibits moderate activity against anaerobes and mycobacteria. Sparfloxacin is well tolerated and the intake of food has no adverse effect on the pharmacokinetic features (Blondeau 1999, Stahlmann et al. 1998). For the medical important of this drug author have been study its structure by recording and investigate its electron ionization (EI) mass spectra at different electron energies 70 and 15 eV. Also, the chemical ionization (CI) mass spectrum has been recorded and investigated. The main fragmentation processes in EI and CI have elucidated and discussed. The main fragment ions in EI mass spectra are [M-C4H8N] + and fragment [M- C4H8N- CO2] +, while [MH- CO2]+ ion are the most fragment ion in CI mass spectrum. On the other hand, the molecular structure optimization of sparfloxacin was calculated using the modified neglect of diatomic overlap (MNDO) semi-empirical molecular orbital method. Also, the thermochemical data such as heat of formations, total energy, ionization energy, electron affinity and dipole moment have been calculated and discussed.